Population status of the tree Sacoglottis holdridgei (Humiriaceae) at Isla del Coco National Park, Costa Rica - Acosta-Vargas, Luis Guillermo (2016)
Isla del Coco is the only oceanic island in the Eastern Pacific with humid tropical climate. Its forests have a particular structure with a unique array of plant species and high endemism. There are few studies on the flora or forest monitoring on the island.  The population structure of Sacoglottis holdridgei was analyzed using data from six years with data points taken in 2006 and 2012, including sampling of regeneration in 2012. Sacoglottis holdridgei was the most important tree species, presenting in 2012 the highest Importance Value Index (190.7±21.8), abundance (158.5±40.3 Nha-1 or 39.5 % of the forest) and basal area (15.6 m2ha-1 or 72.9 % of the forest). It was present in all three height strata with dominance in the highest. Annual mortality was reported at 3.3 % and recruitment at 1.2 %. The diameter distribution of forest fits the inverted J model, but not for the reported species of which only S. holdridgei tends to adjust for DBH>40 cm. Regeneration fitted the inverted J model with values below those reported for continental forests. Even though it was the dominant species, S. holdridgei showed low regeneration values. This particular condition, give way hypotheses related to the introduction of species, species biology and climate change which could influence the future development of S. holdridgei and forests of Isla del Coco.